The Rise of China in the 21st Century on Belt and Road Initiative: The Implication to Indonesia Development - Muhammad, Zuliyan; Muhammad Faizal, Alfian; Geng, Weiwei (International Journal of Chinese Interdisciplinary Studies, 2024)
China’s rise is in a high pace today. There is no doubt that the rise is followed by the expansion of China’s foreign policy to other countries. With the great strategy on the Belt and Road Initiative (BRI), China perceives Southeast Asia region as a strategic base on its diplomacy, especially to Indonesia. China sees Indonesia as great power country in ASEAN, as well as a strategic country for China to be its partner in economic expansion. Therefore, this paper is questioning how Indonesia is affected by this great initiative through the implementation of China’s BRI in Indonesia. This essay uses neoliberalism as a theoretical framework to analyze how such international cooperation creates high interdependence amongst states in the international system. The result shows that international cooperation under BRI provides aids and assets for developing states to grow their economy in the future.